2017
DOI: 10.1039/c6cy02676a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of copper and potassium on the structure and carbidisation of supported iron catalysts for Fischer–Tropsch synthesis

Abstract: In silica supported iron Fischer–Tropsch catalysts, promotion with copper strongly enhances both hematite reduction and magnetite carbidisation, while potassium promotion hinders reduction of hematite to magnetite but enhances magnetite carbidisation in carbon monoxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 43 publications
3
59
0
Order By: Relevance
“…[55] It is also used as an active site in the RWGS reaction, which inhibits methane production, in contrast with Co, Ni, and Ru. [55] It is also used as an active site in the RWGS reaction, which inhibits methane production, in contrast with Co, Ni, and Ru.…”
Section: Iron-basedcatalystsmentioning
confidence: 99%
“…[55] It is also used as an active site in the RWGS reaction, which inhibits methane production, in contrast with Co, Ni, and Ru. [55] It is also used as an active site in the RWGS reaction, which inhibits methane production, in contrast with Co, Ni, and Ru.…”
Section: Iron-basedcatalystsmentioning
confidence: 99%
“…The most prominent effect was observed for coimpregnated catalyst (FeK)/CQ. Recently, we found that potassium inhibits the reduction of Fe 2 O 3 to Fe 3 O 4 by synthesis gas and significantly accelerates the formation of carbide . Cooling the catalysts after synthesis gas treatment with simultaneous measurement of magnetization demonstrated that Fe 5 C 2 is the only magnetic phase formed in such conditions (Figure ).…”
Section: Resultsmentioning
confidence: 95%
“…In as‐prepared catalysts, the interaction between an alkali metal and iron oxides strengthens Fe—O bonds thus decreasing iron reducibility . However, the formation of iron carbides is promoted by potassium …”
Section: Introductionmentioning
confidence: 99%
“…Dual promoters usually function synergistically in literatures. Some of work employ a combination of cationic and anionic species, such as alkali metals and S promoter, and some focus on bimetallic promoters such as MnK, CuK, NaZn and so on . Some promoters, such as Mn, were reported with a combination effect on both particle size and local chemical environment, which contribute to catalytic performance in FTO .…”
Section: Introductionmentioning
confidence: 99%